Communications public policies in Brazil: technological adjustment and free speech - Pieranti, Octavio Penna (2008)
Brazilian researchers in the administration field seldom debate communications policies. This article analyzes these policies in a historical perspective from 1964 to our days, using as sources academic and non-academic literature and the existing legislation. It focuses the broadcasting system and the press, based on principles and postulates considered essential to this sector, such as the independence of the press in relation to the state and its interests and participation in the construction of the communications infrastructure. This debate is divided in two original dimensions: technological, referring to the existing infrastructure, and informational, dependent on State regulation of free speech. The article concludes by calling attention to: the questionable character of the Brazilian media¿s independence; the ties between public and private actors and interests; and the intentional confusion between free press and free corporations.